1998
DOI: 10.1016/s0142-9612(98)00088-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness of debonded straight-tapered stems in cemented THA reduces subsidence but not cement damage

Abstract: Although stress analyses have shown that the mechanical endurance of cemented femoral THA reconstructions is served by stems that firmly bond to their cement mantles, retrieval studies suggest that this may be difficult to achieve. Clinical studies with roentgen stereophotogrammetric analyses have shown that stems may gradually debond from their cement mantle. Accepting the fact that stem debonding is unavoidable, stem subsidence and cement stresses can be reduced by increasing stem-cement friction, as indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 20 publications
5
37
0
4
Order By: Relevance
“…The polished stem surface ensures that surface damage to the cement as the stem subsides is minimised. 62,63 This stem behaviour confirms the view 64 that the generally accepted definitions of 'definite loosening', 'probable loosening' and 'possible loosening' 65 cannot be reasonably applied to the polished Exeter stem. According to these definitions, any visible migration of the component is defined as 'definite loosening'.…”
Section: Discussionsupporting
confidence: 70%
“…The polished stem surface ensures that surface damage to the cement as the stem subsides is minimised. 62,63 This stem behaviour confirms the view 64 that the generally accepted definitions of 'definite loosening', 'probable loosening' and 'possible loosening' 65 cannot be reasonably applied to the polished Exeter stem. According to these definitions, any visible migration of the component is defined as 'definite loosening'.…”
Section: Discussionsupporting
confidence: 70%
“…Several computational models have analyzed the influence of stem-cement interface debonding on cement deterioration. 45,46,58 In a polished stem, considering the interface as completely debonded with friction could be a good approach because adherence between the stem and the bone cement is not adequate. On the contrary, in a rough stem, the state of the stem-cement interface is essential to reproduce the subsidence of the stem in the cement mantle and to simulate damage accumulation in the cement.…”
Section: Introductionmentioning
confidence: 99%
“…With its geometric properties, a polished tapered stem is likely to distribute the vertical stress caused by load in the horizontal direction and to increase the compressive stress [5,9]. In addition, having a tendency to cause taper slip and stress relaxation, a polished tapered stem has less shear stress at the cementbone interface [5,9,10,[13][14][15][16] and causes stem subsidence without cement fracture. It is presumed that if stem subsidence occurs without cement destruction or loosening, the cement moves in the femoral canal [5,9,16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, having a tendency to cause taper slip and stress relaxation, a polished tapered stem has less shear stress at the cementbone interface [5,9,10,[13][14][15][16] and causes stem subsidence without cement fracture. It is presumed that if stem subsidence occurs without cement destruction or loosening, the cement moves in the femoral canal [5,9,16]. Basic experiments have found that PMMA cement moves, or creeps, after polymerization [8,9,12,15].…”
Section: Discussionmentioning
confidence: 99%